Design of Experiment-Based Optimization in Formulation of Atorvastatin Solid Dispersion using Linum usitatissimum Seed Gum: Solubility Enhancement of Atorvastatin by Solid Dispersion Technique - Bora, Ramarao; Siragam, satyalakshmi (Iranian Journal of Pharmaceutical Sciences, 2026)
Solid dispersion (SD) is the most promising approach for enriching the drug release of poorly soluble drugs. Atorvastatin (ATR) is a lipid-lowering drug, but its low water solubility hinders its dissolution and effective treatment. In this study, flaxseed gum (FSG) derived from Linum usitatissimum has been investigated as a potential carrier for SD formulations to overcome solubility limitations. A modified hot extraction procedure was employed to isolate FSG, which was subsequently characterised for its physical properties. Design of experiments was conducted using Response Surface Methodology (RSM), with FSG concentration, solvent volume, and temperature as independent variables to optimize the SD formulation via the solvent evaporation technique (SEV). In contrast, the percentage of drug release in 30 minutes serves as the response variable. The formulations were assessed for product quality parameters, and the optimized SD formulation was characterized physicochemically. 33.8 mg of FSG, 8 mL of solvent (ethanol), and 42.5°C were identified as critical quality attributes through RSM. The optimized ATR-SDs formulation exhibited 92% drug release in 30 minutes, 98% drug content, and 1.53-fold improved solubility than pure ATS. Differential scanning calorimetry and x-ray diffraction analysis showed that the drug crystalline form transformed to an amorphous state, while scanning electron microscopy images revealed increased porosity in SD. The current research has demonstrated that the SD of ATR employing a natural carrier could be a promising formulation for enhancing solubility and dissolution.